Implementation of the Children's Digital Literacy Corner Program in Bontoala Village - Ibrahim Nur; Nasrullah Muh; Nasaruddin Hasyim (Journal of Public Policy and Local Government (JPPLG), 2026)
Implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency. This study aims to describe the implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, and to find out the supporting and inhibiting factors of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, with 7 informants. Observation, interview, and documentation methods were used in this data collection process. Data is analyzed through data condensation, data presentation, and drawing conclusions. This study confirms that in the implementation of the children's digital literacy corner program in Bontoala Village, Pallangga District, Gowa Regency, it is seen from the indicators, namely preparation, implementation, monitoring and evaluation, as well as audience and mentoring running "well." In the program preparation stage, namely, the suitability of the literacy corner program with the needs of children as well as the creation of media and socialization needed to support the success of the program, the implementation stage is to include digital education for children with various methods. The third is monitoring and evaluation, namely, to measure the effectiveness of the program that has been implemented to be able to know the extent to which the program's goals are achieved, and finally is audience and assistance. The program is carried out through collaboration with the village and the government but has not run optimally due to insufficient resources and limited community engagement in the activities. The supporting factors for this program include the involvement of the village government, community enthusiasm, and support from activity facilitators. Meanwhile, the inhibiting factors are limited facilities and infrastructure, lack of adequate assistance, and lack of information related to the program, which hinder the program's effectiveness and outreach within the community, ultimately leading to decreased participation and engagement from community members.